Tantangan Program Klinik Sanitasi di Era Society 5.0: The challenge of Sanitation Clinic Programme in the Era of Society 5.0 - Pitriyanti, Luh; Daswito, Rinaldi (JURNAL ILMU DAN TEKNOLOGI KESEHATAN TERPADU, 2024)
This editorial attempts to delineate the obstacles faced by the Sanitation Clinic program in the era of technology advancements in Era Society 5.0. The Sanitation Clinic is one of the environmental health services provided by Puskesmas. The sanitation clinic serves as a specialized clinic for the care of diseases related to the environment. The sanitation clinic is a comprehensive initiative combining promotive, preventive, and curative health services targeting vulnerable populations to address diseases caused by unsanitary living conditions. This initiative is implemented by health center personnel in collaboration with the community, both within and outside the clinic premises, through both passive and active approaches. The sanitation clinic faces challenges while supporting disease control, particularly in limiting disease transmission based on environmental factors. Enhancing collaboration, augmenting the sanitarian workforce, addressing knowledge gaps, and providing sufficient financial backing are necessary for improving sanitation clinics. Furthermore, it is imperative to employ technology to confront the era of the 5th industrial revolution and formulate more efficient environmental health policies using sanitation clinics.